الكلمات الملايوية ذات أصل عربي في قاموس دايا والاستيفادة منها في تعليم اللغة العبية للملايويين المبتدئين في حرف إي نموذجا - Nurmia Nasution; Meitha Kartika Herdiyanti (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2018)
Arabic had entered Indonesian because of Islam which was brought by the Arab traders around the 7th century. The inclusion of Islam in the midst of the society had a considerable influence, especially among the malays people who are Muslim majority. In this study, the researcher tryed to explore 50 Malay words which are borrowed from Arabic in “Daya” dictionary, from letter A, and followed by an analysis of the meanings and changes in the pronunciation of each word, and the method used in this study has an analitycal descriptive approach that proved that there were some many loan words in Malay that are similar to Arabic, but in some words there were changes in the way of pronunciaton, and there has expansion of the meaning, the narrowing of the meaning or complete change in the meaning. This research also proved that these loan words have a considerable role to facilitate the process of learning Arabic for Malay students such as the introduction of Malay words derived from Arabic, and they use these words in the conversation, reading text, evaluation, and make it a tool to explain the meaning of Arabic that students have not understood.